2014
DOI: 10.1136/bmj.g3656
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and mortality: meta-analysis of individual participant data from a large consortium of cohort studies from Europe and the United States

Abstract: Objective To investigate the association between serum 25-hydroxyvitamin D concentrations (25(OH)D) and mortality in a large consortium of cohort studies paying particular attention to potential age, sex, season, and country differences.Design Meta-analysis of individual participant data of eight prospective cohort studies from Europe and the US. Setting General population.Participants 26 018 men and women aged 50-79 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
277
5
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(327 citation statements)
references
References 38 publications
(50 reference statements)
22
277
5
9
Order By: Relevance
“…However, it is uncertain how much these differences are related to different ultraviolet B exposure, vitamin D consumption in the diet, and vitamin D fortification habits in the countries or are just artefacts of the different 25(OH)D assays employed. 2 Surprisingly, a recent meta-analysis confirmed that population means of 25(OH)D concentrations are higher in northern than in southern Europe, as it was also reported by Seneca study, a previous important European cohort study. 3 The Authors of this latter study mainly suspected country differences in vitamin D fortification of foods, such as margarine, as possible causes of the large regional differences.…”
Section: Vitamin D Insufficiency and Deficiencymentioning
confidence: 58%
See 2 more Smart Citations
“…However, it is uncertain how much these differences are related to different ultraviolet B exposure, vitamin D consumption in the diet, and vitamin D fortification habits in the countries or are just artefacts of the different 25(OH)D assays employed. 2 Surprisingly, a recent meta-analysis confirmed that population means of 25(OH)D concentrations are higher in northern than in southern Europe, as it was also reported by Seneca study, a previous important European cohort study. 3 The Authors of this latter study mainly suspected country differences in vitamin D fortification of foods, such as margarine, as possible causes of the large regional differences.…”
Section: Vitamin D Insufficiency and Deficiencymentioning
confidence: 58%
“…2 These data evidence that it is difficult to identify cut-off values for vitamin D deficiency, namely for 25(OH)D variations by geographic region, sex, and season, factors that might need to be taken into account (Table 1). The American Institute of Medicine (IOM) recommends to distinguish a level of insufficiency [defined as 30-50 nmol/L or 16-25 ng/mL of 25(OH)D] and another of deficiency identified by 25(OH)D levels lower than 30 nmol/L (or <16 ng/mL).…”
Section: Potential Role Of Vitamin D In Prevention Of Skeletal and Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the link between vitamin D deficiency and allcause mortality is well-established [38][39][40][41], the current epidemiological evidence linking endogenous total and free testosterone concentrations to mortality risk among men remains inconclusive. While total testosterone was mostly negatively related to mortality [13,14,16,20,42] with one study reporting a non-significant relationship [22], free testosterone was positively [22] or negatively [5] related to mortality andlimited evidence suggests that SHBG may not be related [22] to mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This led the Scientific Advisory Committee on Nutrition to recommend a daily vitamin D intake of 10 µg for all adults within the UK (1) . CVD is one of the main causes of morbidity and mortality in the world and there is mounting evidence indicating an association between suboptimal vitamin D status and increased risk of CVD (3)(4)(5)(6) and all-cause mortality (7)(8)(9) . However, few prospective cohort studies have analysed the relationship between vitamin D intake and CVD risk and allcause mortality.…”
mentioning
confidence: 99%